Pengaruh Pemberian Probiotik Mikrobioma Seita pada Pakan Pelet terhadap Kelulushidupan dan Pertumbuhan Benur Udang Vaname Pl 10 (Litopenaeus Vannamei) - Andre Syahrul Ramadani; Sumaryam Sumaryam; Didik Budiyanto; Bambang Supriyadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Vaname shrimp (Litopenaeus vannamei) is one of the fastest-growing aquaculture commodities and has become a leading export product in Indonesia. The increasing market demand for vaname shrimp requires continuous efforts to improve production efficiency and shrimp performance. One approach to enhancing shrimp growth and survival is the application of probiotics in feed, which can improve digestive processes, nutrient absorption, and water quality. This study aimed to evaluate the effects of different doses of Seita microbiome probiotics added to pellet feed on the survival rate and growth performance of PL-10 vaname shrimp fry (Litopenaeus vannamei). The experiment was conducted using several probiotic dosage treatments, and the observed parameters included survival rate, weight gain, and water quality indicators. The results demonstrated that the application of Seita microbiome probiotics positively influenced shrimp growth and survival. Among the tested treatments, the probiotic dose of 30 mL/kg feed was found to be the most effective and optimal. This treatment produced the highest average survival rate of 90% and an average weight gain of 2.93 g. Furthermore, water quality remained within suitable ranges for shrimp culture, with temperatures of 28–29°C, dissolved oxygen levels of 6–7 ppm, pH values of 8.0–8.2, and salinity levels of 29–30 ppt. These findings indicate that Seita microbiome probiotics can be utilized as a beneficial feed additive to improve the productivity of vaname shrimp farming.